3-D dam break flow simulations in simplified and complex domains. (March 2020) - Munoz, Daniel Horna; Constantinescu, George
Highlights: 3-D models are more accurate than 2-D models for predicting dam-break problems. Dam break flow may be subject to strong 3-D effects. 3-D simulations can be used to recalibrate 2-D models for dam break flows. Abstract: This paper presents a 3-D, non-hydrostatic, Reynolds-Averaged Navier-Stokes (RANS) model using the volume of fluid (VOF) approach to simulate dam-break flows. Good agreement is observed between the 3-D model predictions and results of dam-break experiments performed in the laboratory. The 3-D model is then applied to predict flood-wave propagation induced by the sudden failure of two flood-protection dams in Iowa, USA. Results are also compared with predictions of 2-D, hydrostatic, depth-averaged models. The 2-D model simulations using the precalibrated values of the Manning's coefficients underpredict the speed of propagation of the flood wave and the area inundated by the flood compared to the 3-D model predictions. A methodology is presented to recalibrate the 2-D model which improves the agreement with the 3-D model predictions. Simulation results also show that strong 3-D effects are generated in regions of strong curvature of the river channel, near sudden constrictions and obstacles, and during the times the mean flow direction varies significantly over the flow depth. Such 3-D effects cannot be captured by the 2-D model even after recalibration, pointing toward the need to use 3-D models for detailed flood mapping.